2015
DOI: 10.1007/s12038-015-9524-6
|View full text |Cite
|
Sign up to set email alerts
|

siRNAs targeting PB2 and NP genes potentially inhibit replication of Highly Pathogenic H5N1 Avian Influenza Virus

Abstract: Highly Pathogenic Avian Influenza (HPAI) H5N1 virus is a threat to animal and public health worldwide. Till date, the H5N1 virus has claimed 402 human lives, with a mortality rate of 58 percent and has caused the death or culling of millions of poultry since 2003. In this study, we have designed three siRNAs (PB2-2235, PB2-479 and NP-865) targeting PB2 and NP genes of avian influenza virus and evaluated their potential, measured by hemagglutination (HA), plaque reduction and Real time RT-PCR assay, in inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Different types of RNAs are expressed in virus-infected cells during an IAV life cycle, including mRNA, viral genomic RNA (vRNA), and complementary RNA (cRNA), all of which can be potential targets for degradation mediated by siRNAs. Various types of siRNAs have been reported to be effective in inhibiting the replication of IAV, including siRNAs specific for PB2, PB1, PA, NP, M1, M2, and NS1 viral genes (25,37,39,(45)(46)(47)(48)(49). However, most of the studies have been based on chemically synthesized single-site siRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of RNAs are expressed in virus-infected cells during an IAV life cycle, including mRNA, viral genomic RNA (vRNA), and complementary RNA (cRNA), all of which can be potential targets for degradation mediated by siRNAs. Various types of siRNAs have been reported to be effective in inhibiting the replication of IAV, including siRNAs specific for PB2, PB1, PA, NP, M1, M2, and NS1 viral genes (25,37,39,(45)(46)(47)(48)(49). However, most of the studies have been based on chemically synthesized single-site siRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, Behera and co-workers observed, using three siRNAs designed against the PB2 and NP gene segments of HPAI H5N1 (identified as PB2-2235, PB2-479 and NP-865), 8-to 16-fold reduction in virus HA titers, 68-80% reduction in viral plaque counts, and 87-94% reduction in RNA copy number for 48 hours (maximum observation period) after challenge with 100TCID50 of virus. 94 Sui et al also reported that inhibition of propagation of H1N1 and HPAI H5N1 viruses in stable cell lines by siRNAs targeting the M2 gene was sustained for more than 50 hours post-infection. 79 Similar results were obtained by Ge et al in MDCK cells using siRNA targeting the NP gene (NP-1496).…”
Section: Broad Anti-influenza Spectrum and Long-term Inhibitory Effectmentioning
confidence: 99%
“…Moreover, coupling siRNAs with various pro-cell carriers to form small molecules can increase the permeability of cells and reduce innate immunity responses [27,31]. In addition, when siRNA is applied to the stem-loop structure of mRNA, the siRNA inhibition rate can be increased [34]. The siRNA designed for M and NS transcripts with primary transcripts exhibited enhanced silencing effect [19].…”
Section: Problems and Prospects Of Sirna In Anti-influenza Viral Infementioning
confidence: 99%